Religious Character-Based Inclusive Education in General Course for Difabel Students at University - Hilman Taufiq Abdillah; Endis Firdaus; Makhmud Syafe'i; Nurti Budiyanti; Yusuf Ali Tantowi (Jurnal Pendidikan Islam, 2025)
This study addresses the need for a character-based inclusive education model that accommodates students with disabilities in higher education, particularly within the Indonesian context. The objective is to design a values-oriented educational framework that integrates moral and religious principles into inclusive teaching practices. Employing a Research and Development (R&D) approach, the study involved general course students at an Indonesian university, with data gathered through interviews, observations, and a review of relevant literature. The findings reveal a hierarchical structure of character values comprising basic values (tolerance, sympathy, empathy), instrumental values (self-awareness and cooperation), and ultimate values centered on sincere service (lillahi Ta’ala). Additionally, the implementation of character education in Islamic and Civic Education courses must be responsive to the unique challenges faced by students with disabilities, requiring curriculum adjustments in terms of learning media, instructional materials, and assessment strategies. The study contributes to the field by emphasizing ta’awun (mutual assistance) as a core religious value that underpins inclusive relationships among faculty, students with disabilities, their peers, and families, thereby promoting a more compassionate and supportive academic environment.